Pelatihan Membatik Sebagai Wujud Pengembangan SDM Dalam Upaya Melestarikan Kebudayaan Batik di Kelurahan Menanggal Surabaya - Thalita Alsa Dilla Putri; Virginia Mandasari; Ayundha Evanthi (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
Indonesia is a multicultural country with various arts and cultures in it. It is the responsibility of all parties to maintain this cultural heritage so that it remains sustainable. One of the proud heritages of the Indonesian people is batik. Batik is a characteristic that has become the identity of the Indonesian people. The increasingly sophisticated technology has made many people lose interest in Indonesian arts and culture. The lack of participation of the younger generation in the preservation of batik culture has led to the decline in the existence of batik, especially written batik, among the community. One of the areas that tries to maintain the existence of batik culture is Menanggal Village with the establishment of Sanggar Batik Modern Menanggal, but the lack of human resources is an obstacle to the realization of batik preservation. In response to this, UPN "Veteran" East Java students in the Real Work Lecture program conducted socialization activities and batik training for the local community as a form of community service. This paper aims to provide an overview of batik socialization and training activities with children as the target as a form of human resource development in an effort to preserve batik culture in Menanggal Village, Surabaya City. With the potential that Kelurahan Menanggal has, the human resource factor which is the main factor should be given more attention.